Differences in Knowledge of Mothers with Small Babies Regarding Small Baby Care in Areas Using and Not Using the Special Maternal Child Health Handbook for Small Babies - Sari, Nissa Prima; Amir, Arni; Mayetti, Mayetti (Frontiers on Healthcare Research, 2026)
Background: The implementation of the special Maternal and Child Health (MCH) Handbook for small babies has been introduced in several regions in Indonesia. This is because the existing MCH Handbook, which is widely used in Indonesia, has not fully accommodated the needs of mothers and families as a guide for caring for and monitoring small babies. This study aims to analyze the differences in knowledge of mothers with small babies regarding small baby care in areas using and not using the special MCH Handbook for small babies. Methods: This study employed a cross-sectional comparative design. The study was conducted in the working area of Tanjung Paku Public Health Center in Solok City, West Sumatra, Indonesia, as the group using the special MCH Handbook for small babies, and in the working area of Pariaman Public Health Center in Pariaman City, West Sumatra, Indonesia, as the group not using the special MCH Handbook for small babies. The study was conducted from September to October 2024. The required sample size was 46 participants per group, with a total of 92 participants. A simple random sampling technique was used. Data were analyzed using the Mann-Whitney test, with a significance level of P<0.05. Results: The median total score for maternal knowledge about small baby care in areas using the special MCH Handbook was 14, higher than the score of 12 in areas that did not use the handbook. A significant difference was found in maternal knowledge regarding small baby care between areas using and not using the special MCH Handbook (P<0.05). Conclusion: There is a significant difference in the knowledge of mothers with small babies regarding small baby care between areas using and not using the special MCH Handbook for small babies. Strengthening policies and promoting the importance of the special MCH Handbook for small babies is crucial to improving maternal knowledge in small baby care, especially in areas with high rates of preterm births.